Harnessing Research Pressure: A Dual Chain Mediation Effects of Achievement Motivation and Research Anxiety on Innovative Behavior Under Challenge-Hindrance Research Stressors - Ma J; Hu L (Psychology Research and Behavior Management)
Jikang Ma,1,* Luping Hu2,3,* 1College of Business Administration, Anhui University of Finance and Economics, Bengbu, Anhui, People’s Republic of China; 2School of Public Administration, Xiangtan University, Xiangtan, Hunan, People’s Republic of China; 3Postdoctoral Workstation, Zhejiang Institute of Mechanical and Electrical Technician, Jinhua, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Luping Hu, School of Public Administration, Xiangtan University, North Second Ring Road, Yuhu District, Xiangtan, Hunan, 411105, People’s Republic of China, Email lupinghu2024@163.comPurpose: As high-caliber innovative talents in the era of China’s new quality productivity, researchers often face substantial pressures in their academic work. However, a critical question arises: does research pressure influence their innovative behavior, and if so, through what mechanisms? Despite its significance, few scholars have addressed these issues in depth. Grounded in the cognitive transactional theory of stress and adopting a “perception → psychology → behavior” research framework, this study develops a dual chain mediation model to explain the association between challenge-hindrance research stressors and researchers’ innovative behavior.Patients and Methods: A two-wave survey was conducted, collecting 887 valid responses from researchers across 30 provinces in China. To evaluate the proposed hypotheses, structural equation modeling (SEM) was employed alongside a bootstrap analysis conducted via SPSS and M-PLUS. These methods provided rigorous validation of the relationships and mechanisms underpinning the dual chain mediation model.Results: The findings reveal that challenge research stressors positively and significantly influence researchers’ innovative behavior, mediated by achievement motivation and research anxiety. Conversely, hindrance research stressors negatively and significantly impact innovative behavior through the same dual mediating paths. Additionally, achievement motivation exerts a negative effect on research anxiety, while the dual chain mediation of achievement motivation and research anxiety plays a pivotal role in linking both challenge-hindrance research stressors to innovative behavior.Originality: This study reveals that challenge- and hindrance-oriented research stressors shape researchers’ innovative behavior through intertwined psychological pathways of achievement motivation and research anxiety. Notably, we identify that achievement motivation both mitigates anxiety and functions as a chain mediator linking stressors to innovative outcomes. These findings advance knowledge on fostering creativity during the era of New Quality Productivity, offering evidence-based guidance for research-oriented organizations and managers in China seeking to enhance innovative performance.Keywords: challenge-hindrance research stressors, achievement motivation, research anxiety, new quality productivity, innovative behavior